IMPLIKASI PENARIKAN DIRI AMERIKA SERIKAT DARI JOINT COMPREHENSIVE PLAN OF ACTION ( JCPOA) - Makruf Baiturohim (UNIDA Gontor, 2021)
The decades-long con ict between Iran and the United States (US) over the Iranian nuclear program was tempered by the Iran Nuclear Deal. The Iran Nuclear Deal or be er known as the Joint Comprehensive Plan of Action (JCPOA) was signed by Iran with the P5 + 1 group of countries, namely the United States, Britain, France, China, Russia, and Germany on July 14 2015 in Vienna, Austria. The deal allows Iran to maintain a substantial portion of its nuclear infrastructure within certain limits - speci cally its ability to enrich uranium into ssile material, a material required in nuclear weapons. On its way, the US under the leadership of Donald Trump on May 8 2018 decided to withdraw from the deal on the grounds that this agreement was the result of terrible Iranian negotiations that would not bring calm and peace. The formulation of the issues raised relates to the implications of US withdrawal from the Iran nuclear deal. This study uses a normative juridical method by emphasizing the use of secondary data sources as the main reference. The approach method uses a conceptual approach, case approach, agreement approach, and historical approach. The results showed that the US withdrawal from this deal accompanied by the reimposed of sanctions against Iran had implications for disrupting the Iranian economy which resulted in Iran’s decision to no longer comply with and implement the existing deal. The incidents that recently happened to important gures in Iran as a result of the actions of the US have also increased the tension of the con ict as Iran has increasingly shown its activities in the nuclear program which crossed borders. The US withdrawal from the deal constitutes a form of diplomatic vandalism that does not need to occur considering its impact on global stability and conduciveness.